Discovery of novel BET inhibitors by drug repurposing of nitroxoline and its analogues. Issue 44 (31st October 2017) - Jiang, Hao; Xing, Jing; Wang, Chen; Zhang, Hao; Yue, Liyan; Wan, Xiaozhe; Chen, Wei; Ding, Hong; Xie, Yiqian; Tao, Hongru; Chen, Zhifeng; Jiang, Hualiang; et al.
Abstract : The BET family of bromodomain-containing proteins (BRDs) is believed to be a promising drug target for therapeutic intervention in a number of diseases. Abstract : The BET family of bromodomain-containing proteins (BRDs) is believed to be a promising drug target for therapeutic intervention in a number of diseases including cancer, inflammation and cardiovascular diseases. Hence, there is a great demand for novel chemotypes of BET inhibitors. The drug repurposing strategy offers great benefits to find inhibitors with known safety and pharmacokinetic profiles, thus increasing medicinal chemists' interest in recent years. Using the drug repurposing strategy, a BRD4-specific score based virtual screening campaign on an in-house drug library was conducted followed by the ALPHA screen assay test. Nitroxoline, an FDA-approved antibiotic, was identified to effectively disrupt the interaction between the first bromodomain of BRD4 (bromodomain-containing protein 4) and acetylated H4 peptide with IC50 of 0.98 μM. Nitroxoline inhibited all BET family members with good selectivity against non-BET bromodomain-containing proteins, thus it is defined as a selective BET inhibitor. Based on the crystal structure of the nitroxoline-BRD4_BD1 complex, the mechanism of action as well as BET specificity of nitroxoline were determined. Since the anticancer activity of nitroxoline against MLL leukemia, one of the BET related diseases, has not been studied before, we tested whether nitroxoline might serve as a potential repurposing drug candidate for MLL leukemia. Nitroxoline effectively inhibited the proliferation of MLL leukemia cells by inducing cell cycle arrest and apoptosis. The profound efficacy is, at least in part, due to the inhibition of BET and downregulation of target gene transcription. Our discovery of nitroxoline as a BET inhibitor suggests potential application of nitroxoline and its derivatives for clinical translation in BET family related diseases.